Changing NPP consumption patterns in the Holocene: From megafauna-'liberated' NPP to 'ecological bankruptcy'. (December 2016) - Doughty, Christopher E; Faurby, Søren; Wolf, Adam; Malhi, Yadvinder; Svenning, Jens-Christian
There have been vast changes in how net primary production (NPP) has been consumed by humans and animals through the Holocene. Here we ask: how much NPP energy may have become available following the megafauna extinctions? When did humans, through agriculture and livestock, consume more NPP than wild mammals? When did humans and wild mammals use more energy than was available in total NPP in each country? The megafauna extinctions potentially liberated 2.2–5.3% of global NPP that early humans eventually consumed. By 1850, humans began to consume more than wild mammals (globally averaged). Currently, >82% of people live in 'ecologically bankrupt' countries where all plant production could not satisfy our energy demands. To summarize, we began the Holocene with an NPP energy surplus, became the dominant consumers of NPP over the natural world by the start of the Industrial Revolution, but now consume more total energy (including fossil fuels) than is available in NPP in most countries.